Cultural and Archaeological Heritage, Landscapes and Root Tourism Building the Enhancement of Territories - Mancuso, Stefania (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2023)
This paper emphasizes the development of cultural heritage in order to construct a planned, emotional and sustainable use. Starting from a general reflection on the value and use of cultural heritage for the recognition of the territories and their culture, this work, wants to contribute to the debate on tourism of the roots and on the methods by which it is possible to construct a functional cultural offer for the development of this particular form of tourism, by analysing the territory of Calabria. Although certain subjects are common to those currently discussed in the specific cultural sphere, the tourism of roots may usefully define perspectives, operating practices and methods based on cultural heritage or consolidate and clarify those already in place. Actually, it can draw new attention to cultural heritage by generating the so-called "place attachments", to help identify new approaches and models for 'culture oriented' development. Particular emphasis is placed on the archaeological heritage of the region, analysing the evolution of scientific research through the work of Paolo Orsi (First Calabrian Superintendent) carried out between the late nineteenth and early twentieth century. However, all the organisation results in terms of usability have been achieved since the 1980s of the last century. By analysing the current system of valorisation of Calabria composed by museums, archaeological zones and parks, of state or local jurisdiction, taking into account the entries of state structures in the area along the limited evidence available, we will attempt to define what of type interest can activate the tourism of the roots on the archaeological heritage or how much the latter can contribute to consolidate the sense of belonging to the territory, evident in the tourism of the roots. In many Italian towns not characterised by over tourism, the enhancement of cultural heritage, especially archaeological, implies a new awareness in the territories where community participation can contribute to cultural, environmental, political and economic transformation. The stakes associated with the tourism of the roots converge towards a new logic of valorisation of the archaeological heritage, which is no longer only passive and detached. The new trend is now to make every visitor from any origins and social background actors in knowledge transfer and awareness of the value of cultural heritage; and even more the tourist of the roots could usefully participate in this process of re-appropriation, rediscovery and enhancement through what is called "public archaeology" form , which appears to be the most appropriate tool for creating new synergies and linkages between the territory and the communities, including the Rootists